Sistem Pendeteksi Tangan Berbasis Mediapipe Dan OpenCV Untuk Pengenalan Gerakan - Arif, Muhammad; Saum Haryono, Gemilang; Fawwazi Arsyad, Naufal; Ramadhani Airmas Sahid, Rubby; Rosyani , Perani (CV. Shofanah Media Berkah, 2024)
This project aims to develop a real-time hand detection system using Mediapipe and OpenCV technology. This system is able to detect hands, identify hand landmark positions, and calculate numbers based on finger positions. This implementation makes important contributions to gesture recognition and human-computer interaction applications.